Estudio cibermétrico sobre el impacto y posición institucional del CSIC en el web - Aguillo, Isidro; Granadino, Begoña (Revista General de Información y Documentación, 2004)
The objective of this work is the study of the presence of the CSIC on the Web. The cybermetric indicator used are based on the stimation of the volume of the contents in the different institutional CSIC subdomains and on the quantification of the hypertextual nature of the Web pages of these subdomains. The areas of Biology and Biomedicine, Natural Resources and Science and Technology for Physics are the areas of greatest size and visibility on the Web whereas Agrarian Sciences and Science and Food Technologies are areas of less Web size and visibility. The CSIC, according to the Alexa Ranking, is at position 6.857 of popularity and the main CSIC web page and the CINDOC web pages are the pages with the greatest contribution.